Isolasi Fungi Endofitik Pada Organ Kulit Batang Tanaman Gambir (Uncaria guianensis (Hunter) Roxb) - Habisukan, Ummi Hiras; Nisa, Khoirun; Rosa Lia; Oktariyani Putri; Bella, Eken Vegita; Tini Karisma (Universitas Bengkulu, 2023)
Gambir (Uncaria guianensis (Hunter) Roxb) is a shrub from the Rubiaceae family which has hard, twisting stems, short-stemmed leaves, light green in color, small white flowers with round cobs. Gambir is already known to have many medicinal benefits. Lots of compounds contained in gambier which are useful as antioxidants. In Indonesia it is used for betel nut besides the betel plant. Another benefit of the gambier plant is as a mixture of medicines for burns, headaches, diarrhea, dysentery, mouthwash, canker sores, and as a skin tanner to prevent decay which makes the skin look softer, more colorful and youthful. This study aims to isolate the types of endophytic fungi found on the bark of the gambier plant and to identify the types of endophytic fungi based on their macroscopic and microscopic characteristics. The research method used in this study was a sample of Gambir (U. guianensis) taken from Hamlet V, Tambang Rambang Village, Rambang Kuang Subdistrict, Ogan Ilir Regency, South Sumatra. The endophytic fungal isolation method used was gambier plant stem bark samples using PDA media. Bark taken from the main stem and branches, exfoliated less than a full circle. The results of this study succeeded in obtaining 5 isolates of endophytic fungi from the bark of gambir (U. guianensis) belonging to 4 different genera, including Trichoderma, Blastomyces, Fusarium, and Alternaria.